DIRECTIONS OF TECHNOLOGICAL AND DEVELOPMENT REGULATORY AND LEGAL INSTRUMENTS OF THE ORGANIZATION ENVIRONMENTAL ACTIVITY IN UKRAINE - Reshetchenko, A.; Teliura, N.; Lomakina, O. (Municipal economy of cities. Series: «Economy science», 2022)
The paper describes a technique for identifying appropriate environmental technology options for populated areas. The substantiation of a technique of a choice of nature protection technical and economic decisions of increase of ecological safety of urban systems is offered. The relative importance of some factors in the implementation of environmental technical and economic solutions to improve the environmental safety of urban systems using the method of analysis of hierarchies as the basis of management and environmental monitoring. The main stages of the methodology are considered, taking into account the purpose, comparative evaluation, calculations, research. The connection between the elements of adjacent levels of hierarchy is described. It is shown that the method of system analysis will reduce the probability of making the wrong decision to make sound technical and economic decisions to improve the environmental safety of urban systems. Technological and organizational-economic tools, especially in terms of nature management, environmental assessment and entrepreneurship, are aimed primarily at implementing effective, efficient measures aimed at overcoming the deep environmental crisis and ensuring conditions for sustainable development of the state. The advantages of the methodological approach include - the ability to link to a single algorithm to justify the solution of data that differ in content (ecological, biological in higher aquatic plants, urban, social and economic) and in the form of presentation (data of direct measurements, statistical and forecast estimates) to develop a single proposal for the application of modern management in practice. Sustainable Development is a concept that at its core is revolutionary, yet unfortunately incredibly difficult to pragmatically define. The history behind sustainable development is one that does not stretch far. Tensions that can be found within the concept of sustainable development are numerous, ranging from its ambiguous and vague definition, to the failure of attaining a universal pragmatic and operational framework. The great challenge that lies ahead with sustainable development is not only the need to educate it to the people, but to first define it in a way people will understand it.